SOSIALISASI PENCEGAHAN STUNTING UNTUK MENGURANGI JUMLAH ANAK STUNTING DI DESA TAMIAJENG - Marodiyah, Inggit; Saputri, Irmayanti Dwi; Budi, Merselina Juli Dwi Setia; Vitara, Dhea Alinda; fadhila, Moh. Rizki; Fachrudin, Moch Fais (Journal of Social Comunity Services, 2024)
Stunting is a serious problem that can affect children's growth and development and have an impact on the development of human resources (HR) in the future. This study aims to increase community understanding of stunting through socialisation and distribution of UHT milk in Tamiajeng Village. The activities were carried out by KKN-P Group 36 Year 2024 by involving Posyandu Cadres, Village Midwives, and other Health Officers. The methods used include observation, making work programs, and permission from related parties, with activities that include face-to-face socialisation of stunting, as well as assistance in Posyandu activities. The results of the activity show that parents who have toddlers understand the impact of stunting on children. So this activity is expected to provide effective education to parents, help reduce the risk of stunting, and build a healthier generation in Tamiajeng Village.